'As others feel pain in their lungs': Albert Camus's The Plague. Issue 1 (2nd January 2021) - Twidle, Hedley
Abstract : This is an account of reading Albert Camus's The Plague in the wake of various real-world epidemics, and from a place, South Africa, that emerges as a kind of mirror image of the north Africa in which the novel is set. It suggests that what seems at first like a simple story is in fact a deeply complex, even contradictory work: one that that absorbs and reflects back as much history and difficulty as the reader is willing to bring to it. While giving postcolonial critiques of the work their due, I explore how and why The Plague still holds energy and meaning for a 21 st -century audience.